How Ready are Postsecondary Institutions for Students who are d/Deaf or Hard-of-Hearing? - Cawthon, Stephanie Washbourn; Schoffstalll, Sarah Joanna; Garberoglio, Carrie Lou (Education Policy Analysis Archives, 2014)
Educational policy in the United States is increasingly focused on the need for individuals to be academically ready for postsecondary education experiences. The focus of these initiatives, however, centers primarily on individuals and their competencies and characteristics, and not on the capacities of postsecondary institutions to serve them. This article uses the lens of students who are d/Deaf or hard-of-hearing (DHH) to explore ways in which college readiness can be conceptualized as overlapping continuums of preparedness for both individuals and institutions. The article first summarizes research on students who are DHH and their readiness across core domains of academic preparation, language and communication, and soft skills. The article then discusses considerations at the institutional level such as accommodations, direct vs. mediated communication, student disclosure rates, and their level of accessibility for students who have a different academic, linguistic, and cultural experience than most institutional infrastructure is designed to serve. We conclude with considerations for future investigation and an expansion of the dialog around readiness and postsecondary education.